2012
DOI: 10.3109/13645706.2012.703955
|View full text |Cite
|
Sign up to set email alerts
|

Is it safe to perform endoscopic band ligation for the duodenum? A pilot study in ex vivo porcine models

Abstract: Routine EBL is not recommended in the duodenum because the risk of perforation is unacceptably high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In addition, this study demonstrated the safety of the EBL procedure. It was reported that EBL was not safe for treatment of the small bowel, as histologic evaluation revealed inclusion of the muscularis propria and serosa by the band-ligator [24,25] . There were no complications or instances of perforation or penetration in the present study, though the study was limited to only six cases.…”
Section: C B Amentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this study demonstrated the safety of the EBL procedure. It was reported that EBL was not safe for treatment of the small bowel, as histologic evaluation revealed inclusion of the muscularis propria and serosa by the band-ligator [24,25] . There were no complications or instances of perforation or penetration in the present study, though the study was limited to only six cases.…”
Section: C B Amentioning
confidence: 99%
“…There are some reports concerning the use of EBL for treating small intestinal bleeding lesions [13,[21][22][23] , though the safety and efficacy of this use has not been established. However, a recent report indicates that EBL is unsafe and unsuitable for hemostasis in the small bowel [24,25] . Therefore, the aim of this study was to retrospectively investigate the safety and efficacy of EBL for the treatment of bleeding lesions in the small bowel.…”
Section: Introductionmentioning
confidence: 99%
“…Successful closure of esophageal, gastric, and colorectal perforations by using EBL has been reported in a small number of patients. [2][3][4][5][6][7][8] TTS clips are available with different functionality, closing force, ability to be rotated, and retention time. 9,10 Technical challenges remain, and exposure and comfort vary.…”
Section: Discussionmentioning
confidence: 99%
“…Significant theoretical risks are also associated with EVL. In porcine models, duodenal banding demonstrated a 100% perforation rate [20] . Additionally, it is suggested that if the entire varix cannot be banded at the time of intervention, there is the risk of creating a wide defect with re-bleeding after sloughing occurs [21] .…”
Section: Discussionmentioning
confidence: 99%
“…A gastroenterologist will encounter these only rarely as they represent only about 0.4% of all variceal bleeding [1] , yet the traditionally reported mortality approaches 40% [2] , underscoring the importance of prompt and effective management. While there have been hundreds of cases reported, most describe bleeding varices secondary to cirrhosis or intrahepatic portal hypertension.…”
Section: Introductionmentioning
confidence: 99%